1975
DOI: 10.1007/bf00429058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeine on human performance, alone and in combination with ethanol

Abstract: The effect of caffeine (300 mg/70 kg) on cognitive, perceptual and motor functions was investigated both alone and in combination with ethanol (0.75 g/kg) in 68 healthy student volunteers of both sexes. A test battery consisting of standing steadiness, simple and complex reaction time, manual dexterity, numerical reasoning, perceptual speed and verbal fluency was used. Placebos for both drugs were included. Caffeine was administered in decaffeinated coffee immediately after finishing drinking the alcoholic bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 10 publications
2
65
1
Order By: Relevance
“…The reported effect of caffeine on psychomotor function is somewhat conflicting (21,24,35), but, in this study, there was no indication that caffeine improved either reaction or movement times. The frequency of withdrawal symptoms (20,22,40) and side effects (21, 24) associated with caffeine, as well as the impaired postural stability (10,41), are in accordance with previous findings. Thus in one study by Franks et al (10), body sway was significantly increased in the young subjects 40 min after ingesting 4.3 mg/kg caffeine, and also elderly subjects in a study by Swift and Tiplady (41) showed an increased body sway on caffeine compared with placebo.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reported effect of caffeine on psychomotor function is somewhat conflicting (21,24,35), but, in this study, there was no indication that caffeine improved either reaction or movement times. The frequency of withdrawal symptoms (20,22,40) and side effects (21, 24) associated with caffeine, as well as the impaired postural stability (10,41), are in accordance with previous findings. Thus in one study by Franks et al (10), body sway was significantly increased in the young subjects 40 min after ingesting 4.3 mg/kg caffeine, and also elderly subjects in a study by Swift and Tiplady (41) showed an increased body sway on caffeine compared with placebo.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of withdrawal symptoms (20,22,40) and side effects (21, 24) associated with caffeine, as well as the impaired postural stability (10,41), are in accordance with previous findings. Thus in one study by Franks et al (10), body sway was significantly increased in the young subjects 40 min after ingesting 4.3 mg/kg caffeine, and also elderly subjects in a study by Swift and Tiplady (41) showed an increased body sway on caffeine compared with placebo. In this study, postural stability was impaired by 25 and 45% with eyes opened and closed, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Acute exposure to ethanol inhibits adenosine re-uptake via a facilitative nucleoside transporter, increasing the extracellular concentration of adenosine (Nagy et al, 1990;Krauss et al, 1993). In humans, the nonselective adenosine receptor antagonist caffeine reduces sleepiness and psychomotor performance impairment produced by moderate-to-high ethanol doses (Franks et al, 1975;Fillmore and Vogel-Sprott, 1995;Liguori and Robinson, 2001;Drake et al, 2003). In rodents, adenosine receptors seem to modulate some of the pharmacological properties of ethanol, such as sedative/ hypnotic effects (El Yacoubi et al, 2003), motor incoordination (Meng and Dar, 1995;Barwick and Dar, 1998;Dar, 2001), and development of rapid tolerance to ethanolinduced motor impairments (Batista et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Acute exposure to ethanol increases the concentration of extracellular adenosine (Nagy et al, 1990;Krauss et al, 1993). Moreover, there is considerable evidence that the co-administration of caffeine (a nonselective adenosine receptor antagonist) can reduce sleep and psychomotor performance impairment associated with moderate-to-high ethanol doses in humans (Franks et al, 1975;Fillmore and Vogel-Sprott, 1995;Liguori and Robinson, 2001;Drake et al, 2003). Furthermore, the combined administration of caffeine and alcohol can increase the development of alcohol tolerance (Fillmore, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine has been shown to reduce simple RT and to improve performance on the SVT (e.g., Warburton 1995;Smith et al 1992;Smit and Rogers 2000;Hewlett and Smith 1999). Alcohol typically lengthens simple RT (e.g., Carpenter 1959;Sutton and Burns 1971;Franks et al 1975;Tzambazis and Stough 2000), although doses below 0.3 mg/kg might speed responding (Lloyd and Rogers 1997). Alcohol might be expected to disrupt SVT performance, at least at higher doses.…”
Section: Introductionmentioning
confidence: 99%